Antioxidant Activities of Thyme Extracts - Wisam, S.U.; Nahla, T.K.; Tariq, N.M. (Pakistan Journal of Nutrition, 2017)
Background and Objective: Many herbs are known to contain large amounts of phenolic antioxidants other than the well-known compounds like vitamin C, vitamin E and carotenoids. Phenolic antioxidants in herbs primarily consist of phenolic acids, flavonoids and catechins. The antioxidant activity of phenolic compounds is primarily due to their redox properties, which can play an important role in adsorbing and neutralizing free radicals, quenching singlet and triplet oxygen or decomposing peroxides. This study was conducted to determine the antioxidant activities of aqueous and ethanolic extracts of thyme using three different methods. Materials and Methods: The thyme seeds were locally obtained, cleaned and ground. About 20 g of ground material was extracted with 250 mL of distilled water or 95% ethanol at the boiling point under reflux for 1 h. The extract was filtered and evaporated at 50°C to compete dryness. Phenolic contents, antioxidant activities and flavonoids were determined. Results: Ethanolic and aqueous extracts of Thymus vulgaris leaves were analyzed for their phenolic and flavonoid contents, which were 20.31, 13.44, 11.39 and 10.31% for ethanolic and aqueous extracts, respectively. The reducing power of aqueous and ethanolic thyme leaves was also determined. The reducing power was enhanced by increasing sample concentration, it was 92.54% for an aqueous extract at 10 mg mL–1 concentration and 94.51% for an ethanolic extract at the same concentration. The aqueous extract showed low chelating capacity compared with the ethanolic extract (50.75 and 66.03, respectively) using the reducing power of EDTA as a reference (93.00) at 10 mg mL–1. Conclusion: Thymus vulgaris is rich in total phenols. The phenolic contents were determined to be much higher in the ethanolic extract than in the aqueous extract, which may be correlated to the solvent used for extraction.